An Investigation of Lithium Distribution in Certain Precambrian Iron Formations - Goodale, Douglas H. (My University, 1971)
Precambrian iron formations from N.W. Ontario and Melville Peninsula, District of Franklin, were analyzed for Li and major elements. The N.W. Ontario samples contain little Li (0.46 to 5.88 ppm) but high percentages of mafic silicates (20 to 50%). The Melville Peninsula samples show the opposite, having higher Li (1.65 to 58.2 ppm) and lower silicate material (0.6 to 25.0%).
Results from acetic acid leaching experiments show that part of the Li in the Melville irons may be removed, indicating Li to be present both by absorption and substitution.
The higher Li abundances in the Melville Peninsula rocks may be attributed to the effect of later intrusive granites.
Keywords: precambrian, iron, material, lithium